2018
DOI: 10.1371/journal.pone.0192694
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum lipoteichoic acid inhibits biofilm formation of Streptococcus mutans

Abstract: Dental caries is a biofilm-dependent oral disease and Streptococcus mutans is the known primary etiologic agent of dental caries that initiates biofilm formation on tooth surfaces. Although some Lactobacillus strains inhibit biofilm formation of oral pathogenic bacteria, the molecular mechanisms by which lactobacilli inhibit bacterial biofilm formation are not clearly understood. In this study, we demonstrated that Lactobacillus plantarum lipoteichoic acid (Lp.LTA) inhibited the biofilm formation of S. mutans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 59 publications
0
72
0
1
Order By: Relevance
“…The antibacterial activity of Lactobacillus has been reported previously; for example, the reported Lactobacillus strains showed antibacterial activity against C. difficile [ 45 ], E. coli [ 46 ], Shigella spp. [ 47 ], P. aeruginosa [ 48 ], and S. aureus [ 49 ]. Recently, Wang et al [ 50 ] isolated L. plantarum from Tibetan yaks and reported an inhibitory effect against Staphylococcus aureus and E. coli .…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial activity of Lactobacillus has been reported previously; for example, the reported Lactobacillus strains showed antibacterial activity against C. difficile [ 45 ], E. coli [ 46 ], Shigella spp. [ 47 ], P. aeruginosa [ 48 ], and S. aureus [ 49 ]. Recently, Wang et al [ 50 ] isolated L. plantarum from Tibetan yaks and reported an inhibitory effect against Staphylococcus aureus and E. coli .…”
Section: Resultsmentioning
confidence: 99%
“…All of the supernatants tested significantly reduced the biomass, and L. paracasei 25.4 was the strain with the highest capacity to affect S. mutans biofilms. Ahn et al [38] also demonstrated that L. plantarum lipoteichoic acid could inhibit the biofilm formation of S. mutans on polystyrene plates stained with CV and on hydroxyapatite discs.…”
Section: Discussionmentioning
confidence: 97%
“…The eradication of polymicrobial biofilms in human vagina is one of the strategies that can be used to impede bacterial virulence and prevent the onset of BV [ 201 ]. Lactobacillus plantarum LTA hampered the formation of S. mutans biofilms on hydroxyapatite discs via the attenuation of the sucrose decomposition [ 35 ]. Moreover, L. plantarum LTA significantly inhibited E. faecalis biofilm formation and preformed biofilm on human dentin slices suggesting that LTA can be employed as a preventive and therapeutic measures for E. faecalis infection [ 202 ].…”
Section: Lipoteichoic Acid (Lta)mentioning
confidence: 99%
“…It has been suggested that these beneficial effects are partly associated with the cell surface-active molecules (SAMs) such as peptidoglycan (PG), lipoteichoic acid (LTA), biosurfactants (BS) and exopolysaccharides (EPS) [ 31 , 32 ]. In fact, Lactobacillus SAMs has been proved to antagonise a plethora of bacterial and fungal pathogens such as Candida albicans, Staphylococcus aureus, Streptococcus mutans , Escherichia coli , Pseudomonas aeruginosa , and Salmonella typhimurium [ 33 35 ]. Therefore, further understanding in Lactobacillus and its derivatives (i.e.…”
Section: Introductionmentioning
confidence: 99%